Loggerhead (Caretta caretta) in the northwest coast of Africa - Ferreira, Inês Mota (2024)
Cabo Verde is home to one of the largest populations of sea turtles in the world and is an important site of the Northeast Atlantic Regional Management Unit (NEA RMU). Caretta caretta is the most frequent species in this area. The data of breeding ecology (67,594 records) collected in the context of monitoring the beaches of Maio Island, between 2012 and 2019 were analyzed. The results demonstrate that the nesting females on this island are smaller, with an average curved carapace length of 79.4±4.0 cm, laying an average of 4.6 nests per season, with 80.4±14.0 eggs per clutch at an average depth of 46.6 cm. The interval of days between each posture is 15 days and the remigration interval is 404±5 days, followed by a value of 700±5 days. Thus, it was estimated that the Maio colony could have more than 6,600 breeding females, highlighting the crucial role of this place for the species Therefore, the importance of collecting and processing data, key elements for conservation, is highlighted, in order to fully unravel and understand NEA RMU’s Caretta caretta and its life cycle. Moreover, scientific knowledge makes it possible to implement more effective conservation measures. The lack of information about sea turtles on the Atlantic coast of Africa, that has been mentioned by some specialists, as well as the low field effort and the lack of studies of nesting ecology, genetics, and telemetry, does not allow to clarify the life cycle of Caretta caretta. More studies are needed to understand all aspects of this species and thus understand the role of this population in the Atlantic and the inter-connectivity with other areas, namely with other Regional Management Units. Cooperation between the various countries in this region is also necessary so that proactive efforts are made to protect the population of this Regional Management Unit, but also to apply international measures to protect sea turtles in all the habitats they occupy along their life cycle.